The material and mental effects of animal disappearance on indigenous hunter-gatherers, past and present. (2nd January 2020) - Halfon, Eyal; Barkai, Ran
ABSTRACT: For indigenous hunter-gatherers, dependent for their subsistence and well-being on prey animals, animal extinction had significant and multifaceted effects, only some of which are reflected in the archaeological record. Contemporary hunter-gatherers often view animals as equal partners in a shared habitat, where these animals are simultaneously hunted and revered. We posit that this same duality existed among past hunter-gatherer groups. The disappearance of a species that supported human existence for millennia triggered not only technological and social changes but also had profound emotional and psychological effects. We present several selected case studies that reflect the complex dual relationship between indigenous hunter-gatherers and their prey under different environmental conditions. We focus on the material and mental effects of animal population decline over diverse cultures, geographies, and time scales. Our study sheds light on the vital role of specific animal taxa in human biological and cultural evolution. It also deepens our understanding of how indigenous hunter-gatherer societies expressed their awareness of coexistence with other species. In the age of the Sixth Extinction, this study might be more relevant than ever not only for reconstructing the life ways of indigenous hunter-gatherers but for all human and nonhuman species populating the planet.